Analisis Hubungan Self-Efficacy Dengan Prestasi Belajar Mahasiswa di STKIP Al Amin Dompu - Nur Islamiati; Yeni Rahmawati (Jurnal LENTERA: Jurnal Studi Pendidikan, 2023)
This study aims to find out how the relationship between self-efficacy and learning achievement. This research approach is a quantitative correlation approach with the type of ex-post facto. This research was conducted at STKIP Al Amin Dompu. The research posulation is all students at STKIP Al Amin Dompu. The sampling technique used random sampling which totaled 30 students. The research instrument used a Likert scale type sheet with a total of 20 items and a description test sheet with a total of 5 items. Data collection techniques using questionnaires and tests. The data analysis technique used the product moment correlation test with SPSS type 29.00 for windows. The results showed that there was a significant relationship between the variable self-efficacy and learning achievement because the significant sig (2-tailed) was less than 0.05 or 0.01 <0.05. r count (Pearson Correlation) is greater than r table or r count > r table which is equal to 0.675 > 0.361 which indicates a relationship or correlation between self-efficacy variables and learning achievement and has a positive relationship. The level of relationship between self-efficacy variables and learning achievement is in the strong criteria